Integrated land use assessment: the case of Klang Valley Region, Malaysia - Yaakup, Ahris; Johar, Foziah; Abu Bakar, Siti Zalina; Sulaiman, Susilawati; Baharuddin, Mohd. Nizam (2005)
The dynamic nature of planning and monitoring of development in Klang Valley, the fastest growing region in Peninsular Malaysia, apparently requires a ‘tool’ for continuous evaluation and analysis of current environment as well as the capacity for future development. As such, the concept of Integrated Land use Assessment (ILA) was introduced through the “Application of GIS for Klang Valley Region” (AGISwlk) project. The ILA model developed is implemented through incorporation with the use of What if?, a scenario-based, policy-oriented planning support system. A user interface is also developed to ease the access and preparation of data from the AGISwlk database to run the ILA model and generate alternative scenarios.